(untitled) (American Journal of Innovation in Science and Engineering, 2025)
The environmental and regulatory problems caused by industrial wastewater containing synthetic dyes such as methylene blue become more complex because these substances remain toxic and persistent while showing resistance to standard biological treatment methods. The research describes the creation of a blockchain-enabled nanocatalyst tracking system that detects and verifies dye pollutants in water streams through real-time monitoring. The system uses semiconductor nanocatalysts with advanced oxidation processes to break down, and uses microcontrollers to process data signals before blockchain protocols store performance metrics, which maintain transparency and immutability, and meet worldwide environmental reporting requirements. The system included a miniaturized reactor chamber with automated fluid management pollutants efficiently while optical and electrochemical sensors track concentration changes and monitor pH and temperature levels. The system and wireless blockchain connectivity in its compact design. The system achieved 85% methylene blue degradation in controlled tests while sensor data showed pseudo-first-order kinetics and maintained high calibration stability. The system performed well in power efficiency tests while showing fast blockchain transaction speeds and it maintained stability through different operational settings. The cost evaluation showed that the system operates within budget while environmental studies demonstrated better carbon emission performance than traditional monitoring systems. The proposed framework combines nanocatalytic water treatment with blockchain-based data tracking to create a sustainable wastewater management system which works for municipal treatment facilities and industrial sites and decentralized monitoring systems. The integration of environmental nanotechnology with digital compliance systems through this innovation enables the development of self-regulating water treatment systems for the next generation.